A Study on Internet of Things (IoT) Threats - Reddy.S, Vikas; S.N, Chandrashekara. (International Journal of Engineering and Technology, 2018)
This paper is mainly related to the threats that are trending on the Internet due to many objects being connected. There are many threats which are discussed in this paper and the main one would be privacy invasion, that is attacking the data by the attackers on the Internet. The solutions would be using authentication keys on both the ends using technologies such as arduino, wireshark, secure databases and secure protocols. The different applications of Internet of Things (IoT) are in health-care management and in our daily activities. Hence we apply security measures so that all the data will be secured and the users can happily interact.Â Â